2003
DOI: 10.1093/occmed/kqg089
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave analysis among self-employed Dutch farmers

Abstract: The results make it easier to identify groups of farmers to be targeted to prevent sick leave. To reduce the occurrence of sick leave in agriculture, the strategy should be to prevent musculo-skeletal injuries and disorders. Furthermore, a sector-specific approach is recommended, so that preventive actions can be focused on working conditions-specifically on workload and work safety. Efforts to shorten the duration of sick leave will also be valuable to obtain a reduction of sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 11 publications
1
35
1
Order By: Relevance
“…In several studies, age was positively related to increased sick leave [4,12,24]. In contrast, our findings show that the chance of getting sick leave for younger workers was higher than for older ones.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In several studies, age was positively related to increased sick leave [4,12,24]. In contrast, our findings show that the chance of getting sick leave for younger workers was higher than for older ones.…”
Section: Discussioncontrasting
confidence: 87%
“…Hartman, Oude Vrielink, Huirne, et al showed that MSDs were the major reason for a significant part of sickness absences [4]. Seferlis, Németh, Carlsson, et al showed that sick leave episodes related to MSDs were fourfold more frequent in workers that suffered from chronic low back pain [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study among self-employed insured farmers revealed that neck, shoulder, upper extremity, and back disorders accounted for 30% of the claims for sick leave of less than 1 year [Hartman et al, 2003]. Furthermore, 18-20% of the farmers who filed a claim were still on sick leave after 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study showed that the incidence of sick leave in general varied highly between the agricultural sectors [Hartman et al, 2003]. Given the variety mentioned above in types of farms in the Dutch agricultural sector, it is likely that the exposure to risk factors varies between the types of farming.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 61% of the sick leave claims filed by farmers in the Netherlands were due to a musculoskeletal injury or disease (Hartman et al 2003). Walker-Bone and Palmer (2002) reviewed the latest epidemiological studies in order to estimate the risk for each type of disorder in conjunction with farming in general or specific risk factors.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%